2016
DOI: 10.3390/antiox5020017
|View full text |Cite
|
Sign up to set email alerts
|

Berry Leaves: An Alternative Source of Bioactive Natural Products of Nutritional and Medicinal Value

Abstract: Berry fruits are recognized, worldwide, as “superfoods” due to the high content of bioactive natural products and the health benefits deriving from their consumption. Berry leaves are byproducts of berry cultivation; their traditional therapeutic use against several diseases, such as the common cold, inflammation, diabetes, and ocular dysfunction, has been almost forgotten nowadays. Nevertheless, the scientific interest regarding the leaf composition and beneficial properties grows, documenting that berry leav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
160
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(168 citation statements)
references
References 61 publications
2
160
0
6
Order By: Relevance
“…Despite their traditional use, leaves are rarely used nowadays, in contrast to berry and fruits [2] or other plant organs such as roots or stems, which are considered food with significant health benefits conveyed by antioxidant activity.…”
Section: Antioxidant and Antiacetylcholinesterase Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Despite their traditional use, leaves are rarely used nowadays, in contrast to berry and fruits [2] or other plant organs such as roots or stems, which are considered food with significant health benefits conveyed by antioxidant activity.…”
Section: Antioxidant and Antiacetylcholinesterase Activitymentioning
confidence: 99%
“…Plants have been globally utilized since antiquity for flavoring, coloring, and preserving foods and also for food production, cosmetic, and medicinal purposes [1]. Traditional medicine uses roots and leaves as they are rich in bioactive compounds and excellent sources of compounds such as triterpenes, iridoids, xanthones, carotenoids, and benzophenones [2][3][4]. Polyphenolic compounds such as phenolic acids and flavonoids are still among the crucial compounds exhibiting high antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human studies were also reported regarding the cardioprotective activity of bilberry leaves [68]. In a human study of 35 volunteers, Erlund [69] investigated the effects of daily consumption of mixed bilberries (100 g) and nectar containing 50 g crushed lingonberries on well-established risk factors of CVD, such as platelet function, HDL cholesterol, and blood pressure for 2 months.…”
Section: Cardioprotective Activitymentioning
confidence: 99%
“…leaves have traditionally been used in folk medicine for several purposes, including diabetes. It has been shown that water and butanol extracts of the berry leaves are active in T2DM [24]. In one experiment, different extracts exerted a hypoglycemic effect in normoglycemic and alloxan-induced diabetic animals as well [25].…”
Section: Introductionmentioning
confidence: 99%